Reassessing Schistosoma worms: the overlooked role in host pathology and disease elimination - Haoran Zhong; Zhiqiang Fu; Jinming Liu; Yamei Jin (Infectious Diseases of Poverty)
Abstract Background Schistosomiasis, a neglected tropical disease, remains a pressing global health challenge, hindering progress toward achievement of the Sustainable Development Goals (SDGs) in endemic regions. Despite advances in control strategies, including preventive chemotherapy and integrated measures, the elimination of schistosomiasis remains an elusive goal. Current understanding of schistosomiasis pathogenesis has largely focused on egg-induced pathology, while the contributions of schistosome worms to disease progression are relatively underexplored. The objective of this article is to highlight the critical, yet overlooked, role of schistosome worms in disease progression and to advocate for a broader research focus on their direct impact on host pathology and efforts towards disease elimination. Main text Single-sex schistosome infections, which may occur in low-transmission areas, deserve greater attention as they evade traditional egg-based diagnostics. These infections also provide a valuable model to explore the direct contributions of worms to host pathology. Recent studies suggest that schistosome worms, via their excretory-secretory products (ESPs), contribute to liver inflammation, fibrosis, and immune modulation independent of egg deposition. Understanding the interactions between worms and hosts is essential for elucidating their role in disease progression. Furthermore, the potential similarities between schistosome ESPs and those of carcinogenic trematodes highlight the need for further investigation into their long-term impact on host health and schistosomiasis pathology. Conclusions Expanding the focus of schistosomiasis research to include the role of schistosome worms is essential for advancing diagnostic and therapeutic strategies. By incorporating single-sex infection models and targeting worm-derived molecules, it is possible to uncover the overlooked aspects of schistosomiasis pathogenesis, improve diagnostic accuracy, and support global elimination efforts, thereby contributing to the realization of the SDGs. Graphical Abstract